Sistem Pengupahan Pekerja UMKM dalam Perspektif Ekonomi Islam - Siti Nurmala; Saiin Saiin; Seri Yanti Siagian (AL-Muqayyad, 2022)
Raini's UMKM is engaged in the production of toast in Tembilahan Hulu District. A production business has a relationship between workers (wage recipients) and business owners (wage payers). This study aims to determine the principle of wages for workers at Ms. Raini's UMKM and to determine the principles of wages in Islamic. This study uses qualitative research with research subjects namely the owner and 9 workers. While the object of this research is the wage system for workers in the perspective of Islamic economics UMKM, Raini's toast. Data collection techniques with interviews and documentation. The conclusion of the study shows that the wage system for workers in MSMEs producing Raini toast has implemented Islamic wages but has not been maximized. There are still things that must really be considered in the wage system carried out by Ms. Raini's UMKM, such as the initial agreement/agreement regarding the transfer of wages given to workers before starting work.